Essentials marketing research - Zikmund, William G. (Dryden Press, 1999)
This textbook places market research in its social and business context and describes the process of study design, measurement, analysis, and reporting, with coverage of basic sampling and statistical theory. While focusing on traditional marketing research methods, the book also discusses recent innovations and the impact of internet research.